Faktor-Faktor yang Mempengaruhi Pengeluaran Listrik Rumah Tangga - Purnomo, Sigit Dwi (Efficient: Indonesian Journal of Development Economics, 2020)
The condition of the national electricity this center is experiencing a crisis as a result of the surge in demand for electricity is greater than the level of supply. Including for household electricity. The purpose of this study was to determine and analyze the effect of a variable number of electronic goods, household size, amount of space, the building area of the house, and family income over expenditure of household electricity in the village Sekaran, Gunungpati subdistrict, Semarang city. Household electricity expenditure as the dependent variable, while the number of electronic goods, household size, amount of space, the building area of the house, and family income as the independent variable. The method used is multiple linear regression analysis. The results of this study indicate that a variable number of electronic goods, the number of family members, house building area, family income positive effect and significant on household electricity expenditures in the village Sekaran. While the variable amount of space did not affect the household electricity expenditures in the village Sekaran. Kondisi ketenagalistrikan nasional sat ini sedang mengalami krisis sebagai akibat terjadinya lonjakan permintaan akan listrik yang lebih besar dibanding tingkat pasokannya. Termasuk untuk listrik rumah tangga. Tujuan penelitian ini adalah untuk mengetahui dan menganalisis pengaruh variabel jumlah barang elektronik, jumlah anggota keluarga, jumlah ruang, luas bangunan rumah, dan pendapatan keluarga terhadap pengeluaran listrik rumah tangga di Kelurahan Sekaran, Kecamatan Gunungpati, Kota Semarang. Pengeluaran listrik rumah tangga sebagai variabel dependennya, sedangkan jumlah barang elektronik, jumlah anggota keluarga, jumlah ruang, luas bangunan rumah, dan pendapatan keluarga sebagai variabel independennya. Metode yang digunakan adalah analisis regresi linier berganda. Hasil dari penelitian ini menunjukkan bahwa variabel jumlah barang elektronik, jumlah anggota keluarga, luas bangunan rumah, pendapatan keluarga berpengaruh positif dan signifikan terhadap pengeluaran listrik rumah tangga di Kelurahan Sekaran. Sedangkan variabel jumlah ruang tidak berpengaruh terhadap pengeluaran listrik rumah tangga di Kelurahan Sekaran.